AB0906 PREVALENCE OF HYPOVITAMINOSIS D IN DIAGNOSTIC PATIENTS OF BREAST NEOPLASIA IS GREATER THAN EXPECTED FOR THE GENERAL POPULATION? SERIES OF 200 DIAGNOSTIC PATIENTS OF BREAST NEOPLASIA IN A TERTIARY HOSPITAL INITIATING TREATMENT WITH AROMATASE INHIBITORS. (2nd June 2020) - Montero, D.; Ibarguengoitia, O.; Vega, L.; García, C.; Blanco, J. M.; Ruiz, M. E.; Inchaurbe, A. R.; Fernandez, O.; Calvo, I.; Perez, C. E.; García Vivar, M. L.; Cuande, E.; et al.
Abstract : Background: In our population the prevalence of hypovitaminosis D is high. A recent cross-sectional observational study conducted in Spain shows that 63% of postmenopausal women who receive osteoporosis (OP) therapy and 76% who do not receive treatment had 25 (OH) D levels below 30 ng / mL1. The latest studies show a relationship between hypovitaminosis D and the development of systemic inflammatory and tumor diseases, determined by the presence of receptors in various tissues, including breast. Objectives: To determine which levels of serum 25 (OH) D, and secondarily calcium, phosphorus, PTH and CTX, present 200 patients diagnosed with breast cancer and taking hormonal treatment, referred to a monographic OP consultation of a tertiary hospital for the assessment of their bone metabolism, and if these values differ from what is expected for the general population. Methods: Retrospective cross-sectional study of 200 women diagnosed with breast cancer receiving treatment with aromatase inhibitors (AI), performed in a tertiary hospital. Blood levels of vitamin D, calcium, phosphorus, PTH and CTX have been collected, as well as other variables and risk factors. Results: 200 patients with a mean age of 64.8 years and an ED of 9.5 were collected. The median is 64.5 (Q1 58 and Q3 72). The vitamin D levels presented by the study patients were <10 ng/mL in 13 patients (6.67%), 11-20 ng/mL in 50 (25.64%), 21-30 ng/mL in 68 (34.87%), 31-70 ng/mL in 62 (31.79%), and> 70 ng/mL in 2 (1.03%). This implies that in 67.18% of the patients they had values below the optimal range. 92.31% of patients (180) presented PTH values within the normal range and only 7.69% presented values above normal. The serum calcium and phosphorus levels of the patients selected for the study had ranges within normal (99.49%) except 1 case that presented high values (0.51%) for both. The values of CTX (carboxyterminal telopeptide used as a marker of bone resorption) were in the normal range in 81.96% of patients (159), low values in 0.52% (1) and values above the normal range by 17.53% (34). Conclusion: The prevalence of insufficient levels of vitamin D in our study (Breast cancer + AI) is not greater than that estimated for the general population according to various studies. Our study found that 67.18% of patients (2/3 of the selected population) had values below those considered optimal (<30 ng / mL) and 32% had values <20. Only 7.69% of the patients presented PTH values above the normal range. In 82% of patients, CTX used as a marker of bone resorption had normal values. References: [1]Quesada Gomez JM, Díaz Curiel M, Sosa Henríquez M, Malouf-Sierra J, Nogués-Solan X, Gómez-Alonso C, et al. Low calcium intake and insufficient serum vitamin D status in treated and non-treated postmenopausal osteoporotic women in Spain. J Steroid Biochem Mol Biol. 2013;136:175-7. [2]Jian Sun et al., Vitamin D receptor expression in peripheral blood mononuclear cells is inversely associated with disease activity and inflammation in lupus patients; Clinical Rheumatology (2019) 38:2509–2518 Disclosure of Interests: None declared